BS EN IEC 61300-2-24. Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Part 2-24. Tests. Screen testing of ceramic alignment split sleeve by stress application (19th June 2020) - British Standards Institution
No abstract available